2010
DOI: 10.1016/j.vetpar.2010.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Experimental infection by Toxoplasma gondii using contaminated semen containing different doses of tachyzoites in sheep

Abstract: Toxoplasmosis is a parasitic disease caused by Toxoplasma gondii that affects reproductive performance in small ruminants. Although the T. gondii life cycle is well understood since 1960s, several aspects related to its infection remain unclear. In the present study we hypothesized that sheep inseminated with T. gondii-contaminated semen would develop toxoplasmosis. In order to test that hypothesis, 41 sheep were experimentally infected with semen spiked with the organism. Females were divided in three groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 16 publications
1
22
0
3
Order By: Relevance
“…These results demonstrated the sexual transmission of T. gondii among sheep with a consequent vertical transm000ission to the offspring. Moraes et al (2010a and2010b) confirmed venereal transmission of the parasite during insemination with semen that had been experimentally infected with T. gondii and reported reproductive disorders including fetal death, abortion, hydrometra, mucometra, follicular cysts, anestrous and high rates of embryo resorption.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…These results demonstrated the sexual transmission of T. gondii among sheep with a consequent vertical transm000ission to the offspring. Moraes et al (2010a and2010b) confirmed venereal transmission of the parasite during insemination with semen that had been experimentally infected with T. gondii and reported reproductive disorders including fetal death, abortion, hydrometra, mucometra, follicular cysts, anestrous and high rates of embryo resorption.…”
Section: Discussionmentioning
confidence: 70%
“…Since the distribution of T. gondii in tissues from slaughtered animals has already been studied extensively in farm animals, the present study aimed to investigate the presence of this parasite in organs that have not yet been studied, associated with reproductive aspects. The sexual transmission of this parasite was recently proven in association with the experimental infection of sheep (Moraes et al 2010a(Moraes et al , 2010b. This result inspired the performance of the present study, which aimed to detect genomic DNA of T. gondii in the uterus, tubes, ovaries, fetuses and placenta of sheep that were serologically positive and slaughtered in slaughterhouses in the state of Pernambuco, Brazil.…”
Section: Introductionmentioning
confidence: 68%
“…This was agreed by Scarpelli et al [10] who revealed the existence of the parasite in semen samples of animals infected with oocysts (GI) and tachyzoites (GII) which suggest the opportunity of sexual transmission of T. gondii in the bovine species. This also was supported by the isolation of T. gondii in the semen of sheep [9], goats [24] and swine [25]. Moreover, the T.…”
Section: Discussionmentioning
confidence: 70%
“…Vol. 48, No.2 (2017) and placenta of sheep inseminated with infected semen suggesting the potential infection by contaminated semen [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation